Forming digital identities in social networks: the role of privacy concerns and self-esteem. (5th April 2021) - Papaioannou, Thanos; Tsohou, Aggeliki; Karyda, Maria
Abstract : Purpose: This paper aims to identify the data elements that social network sites (SNS) users consider important for shaping their digital identity and explore how users' privacy concerns, self-esteem and the chosen SNS shape this process. Design/methodology/approach: This study conducted an online survey with the participation of 759 individuals, to examine the influence of privacy concerns, self-esteem and the chosen SNS platform, on the shaping of the digital identity, through a classification of identity elements that users disclose when using a SNS, the Rosenberg self-esteem scale and relevant constructs from the literature. Findings: Findings reveal that users consider the name, gender, picture, interests and job as most important elements for shaping their digital identity. They also demonstrate that privacy concerns do not seem to affect the amount of information users choose to publish when shaping their digital identity. Specific characteristics of SNS platforms are found to affect the way that users shape their digital identity and their privacy behavior. Finally, self-esteem was found to affect privacy concerns and digital identity formation. Research limitations/implications: To avoid a lengthy questionnaire and the risk of low participation, the respondents answered the questions for one SNS of their choice instead of answering the full questionnaire for each SNS that they use. The survey included the most popular SNSs at the time of the survey in terms of popularity. Practical implications: The results contribute to the theory by furthering our knowledge on the elements that shape digital identity and by providing evidence with regard to the role of privacy and self-esteem within social networking. In practice, they can be useful for SNS providers, as well as for entities that design security and privacy awareness campaigns. Originality/value: This paper identifies novel factors that influence digital identity formation, including the specific SNS used with its particular characteristics in combination with privacy concerns and self-esteem of the user.